Analisis Pelayanan Perawat Terhadap Kepuasan Pasien JKN Rawat Inap di Rumah Sakit Rafflesia - Agusianita, Agusianita; Nuru, Hasanuddin; Metasari, Des (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2023)
The increase in JKN participants has created a separate problem, especially for private hospitals. An increase in the number of patients that is disproportionate to the number of health workers will have a psychological impact on health workers which can reduce the quality of service, while service will determine the level of patient satisfaction and have an impact on the number of patients seeking treatment at the hospital. The purpose of this study was to determine Nurse Services on the satisfaction of inpatient JKN patients at Rafflesia Hospital. The method used is cross sectional research method. Data was collected by distributing questionnaires to 162 patients using a random sampling technique. The results of the univariate test analysis showed that 74 respondents (45.7%) had good nurse services, 65 respondents (40.1%) said it was quite good, while 23 respondents (14.2%) were not good enough. The results of the Bivariate analysis showed that there was a relationship between nurse service and patient satisfaction